2011
DOI: 10.1111/j.1468-0432.2009.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's Career Success and Work-life Adaptations in the Accountancy and Medical Professions in Britain

Abstract: This article examines gendered career paths in two feminizing and highly qualified professions. Quantitative data show that in medicine the profession is internally segregated by sex, as women tend to opt for the family friendly but clinically inferior specialty of general practice. In accountancy internal segregation by sex is considerably less evident but women fail to rise through organizational hierarchies. Qualitative interviews with qualified doctors and accountants suggest that sex discrimination is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
133
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(141 citation statements)
references
References 35 publications
1
133
0
7
Order By: Relevance
“…Research has shown that women make adaptations to their career goals (e.g., Guillaume and Pochic, 2009) and it is debatable whether career anchors, though socially-grounded, are stable after the very early career years, or whether they may change according to later work experiences. This amounts to the question of whether women's "choices" indeed really are choices or just rationalized constraints (e.g., Crompton and Lyonette, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that women make adaptations to their career goals (e.g., Guillaume and Pochic, 2009) and it is debatable whether career anchors, though socially-grounded, are stable after the very early career years, or whether they may change according to later work experiences. This amounts to the question of whether women's "choices" indeed really are choices or just rationalized constraints (e.g., Crompton and Lyonette, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Medicine represents one case where progress has been seen (Boulis, 2004;Boulis & Jacobs, 2008;Crompton & Lyonette, 2011;Lapeyre & Le Feuvre 2005;Linehan, Sweeney, Boylan, Meghen, & O' Flynn, 2013;Miller & Clark, 2008;Rosende, 2008;Riska, 1993) and Portugal proves no exception (Machado, 2003;Marques, 2011). In the last two decades, the number of women in medicine rose nationally by twelve percentage points, up from 11,385 female doctors (40%), out of a total of 28,326 in 1991 to 23,637 (52%) out of 45,289 in 201345,289 in (PORDATA, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…3 It should be stated at this juncture that not all recent commentators have observed the persistence of sex segregation in the accounting profession. Crompton & Lyonette (2011) found little evidence of it. However they conceded that the aggregate level of their data might explain this.…”
Section: Gender Essentialism and Occupational Segregation In Insolvenmentioning
confidence: 92%
“…While work-life balance continues to dominate academic study and praxis, a number of allied gender issues remain substantially unexplored. Prominent among these, in the wake of the increasing specialisation of professional service provision, is the emergence and consolidation of 'gendered occupational niches' (Crompton & Sanderson, 1986;Crompton & Lyonette, 2011), and the potential ghettoisation of women in particular areas of practice (Roberts & Coutts, 1992;Khalifa, 2004). Our intention in this paper is to augment the sparse literature on gender segregation in accountancy by investigating its presence, and the micro-level processes which sustain it, in a specialist sub-fieldinsolvency practice.…”
Section: Gender Essentialism and Occupational Segregation In Insolvenmentioning
confidence: 99%